2010
DOI: 10.1002/ptr.3198
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plant extracts tested in attention‐deficit/hyperactivity disorder treatment on cell survival and energy metabolism in human neuroblastoma SH‐SY5Y cells

Abstract: Plant extracts like Hypericum perforatum and Pycnogenol ® have been tested as alternatives to the classical ADHD drugs. It has been possible to describe neuroprotective effects of such plant extracts. A reduction of ADHD symptoms could be shown in clinical studies after the application of Pycnogenol ® , which is a pine bark extract. The impacts of the standardized herbal extracts Hypericum perforatum, Pycnogenol ® and Enzogenol ® up to a concentration of 5.000 ng/ml on cell survival and energy metabolism in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The same cells were used in another experiment, in which Pycnogenol and extract from Hypericum perforatum (St. John's wort) were used as alternatives to the classical ADHD drugs. Pycnogenol exerted no significant effect on ATP level but increased cell survival at the concentrations 32.25 and 250 ng/mL [ 124 ].…”
Section: Attention Deficit Hyperactivity Disorders (Adhd)mentioning
confidence: 99%
“…The same cells were used in another experiment, in which Pycnogenol and extract from Hypericum perforatum (St. John's wort) were used as alternatives to the classical ADHD drugs. Pycnogenol exerted no significant effect on ATP level but increased cell survival at the concentrations 32.25 and 250 ng/mL [ 124 ].…”
Section: Attention Deficit Hyperactivity Disorders (Adhd)mentioning
confidence: 99%
“…Mitochondrial activity was evaluated at different times of exposure and substance concentrations. The final results revealed that none of the substances reduced neuronal cell survival compared with control cells [8,9,11]. The activity of LDH enzyme was measured by only one study [11] in which cell death was induced by concentrations of amphetamine (3.50 mM and 5.00 mM).…”
Section: Cell Viability For Neuronal Cellsmentioning
confidence: 96%
“…From the 16 studies selected in our systematic search, five (31.3%) used the SH-SY5Y neuroblastoma [7,8,10,33,34] and two (12.5%) used the PC12 cell line [18,32]. This first strain is a sub-line of the SK-N-SH cell, which was established in culture in 1970 from human metastatic neuroblastoma tissue [35].…”
Section: Neuronal Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…St. John's wort and pycnogenol have been tested as therapeutic alternatives to treat ADHD. A significant increase of SH-SY5Y cell survival was induced by pycnogenol, which did not cause any cytotoxic effect when used in therapeutically relevant concentrations; also, treatment with St. John's wort significantly increased ATP levels [100]. Oroxylin A is a flavonoid isolated from the root of Scutellaria baicalensis Georgi, a herb found in East Asia.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 99%